If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + 9z = 4z + 45 + 2r Combine like terms: 2z + 9z = 11z 11z = 4z + 45 + 2r Reorder the terms: 11z = 45 + 2r + 4z Solving 11z = 45 + 2r + 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. 11z + -4z = 45 + 2r + 4z + -4z Combine like terms: 11z + -4z = 7z 7z = 45 + 2r + 4z + -4z Combine like terms: 4z + -4z = 0 7z = 45 + 2r + 0 7z = 45 + 2r Divide each side by '7'. z = 6.428571429 + 0.2857142857r Simplifying z = 6.428571429 + 0.2857142857r
| -4x-8x=0 | | 4(-1/3)=x | | -3[d-5]=-6 | | (4+56/8x3)/5 | | -6r+4r=-14 | | 3b-q=14+2b | | -n-5n=18 | | 3cb-ca=b-2a | | hj-3j=kforj | | 8x^7/4-56=0 | | -4=-3n+7n | | 1/2=-3/7q | | 18250/6 | | [r-2]=2 | | 8x^2+26x-8=0 | | 4x+12/4-2 | | 9(8d-5)+3=12d-2 | | 3ab-Ac=b-2c | | -6p+8p=-2 | | x^2+y^2-8x-8y+23=0 | | 25=5u-15 | | 12-5+4= | | 1+7b-3=-16 | | -5/18=-5/9+z | | 116=(2x)+(4x) | | -2=2r-2+2r | | 2x-1=z+8-2z | | 3x-x=7-x | | -2/5r=-20 | | 8-8x+3=11 | | 6=f-3 | | 6(3x)= |